2020
DOI: 10.1111/cea.13809
|View full text |Cite
|
Sign up to set email alerts
|

Switching between biologics in severe asthma patients. When the first choice is not proven to be the best

Abstract: During the last decades, new treatments targeting disease mechanisms referred as biologics have been introduced in the therapy of asthma, resulting in a revolution in disease control and medical history. These treatments include monoclonal antibodies, recombinant cytokines and fusion proteins, with the former to be, at the moment, the only approved biological therapy for severe refractory asthma, also included in the disease recommendations. 1 To date, five monoclonal antibodies have been approved for the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 57 publications
0
18
0
1
Order By: Relevance
“…Recent review articles proposed an algorithm to determine the strategy for switching between biologics in patients with severe asthma. 39 Most of the reports have suggested an evaluation period of approximately 4 months. A previous real-world study reported that the efficacy became fixed at 16 weeks in 80% of the cases and within 24 weeks in 90% of the cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent review articles proposed an algorithm to determine the strategy for switching between biologics in patients with severe asthma. 39 Most of the reports have suggested an evaluation period of approximately 4 months. A previous real-world study reported that the efficacy became fixed at 16 weeks in 80% of the cases and within 24 weeks in 90% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…The algorithm recommends switching to omalizumab for patients with atopic manifestations and/or urticaria and switching to dupilumab for patients with FeNO ≥ 25 (ppb) and/or atopic dermatitis. 39 Accordingly, in patients who have residual asthma symptoms despite treatment with a biologic, it is reasonable to switch to other biologics based on positivity for predictive biomarkers and patient characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a lower proportion of atopic asthma can be classified as eosinophilic. 67 Even though there are no guidelines available that provide the efficacy and safety profile of switching among different monoclonal antibodies, a recent review of Papaioannou et al, 68 provides a general overview of different possibilities of switching. Thereby taking into account a summary of clinical, functional and laboratory biomarkers now available, in order to guide clinicians to choose to switch biologics when it is needed and obtain a more efficient response.…”
Section: Discussionmentioning
confidence: 99%
“…However, further understanding is needed on how and when to switch from one biological therapy to another (32). A simple algorithm on switching possibilities in case that the physicians' initial choice is proven not to be the best has been recently suggested by a Greek expert group (33). Moreover, the clinical approach for choosing an initial biologic, the assessment of response to biologics, and the process of troubleshooting and adjusting biologic treatment for those patients with suboptimal responses are discussed in the recent literature (34).…”
Section: Discussionmentioning
confidence: 99%